Capturing Moments in the Social Space of European Integration Training - Häkkinen, Miira; Mikkilä-Erdmann, Mirjamaija (Routledge, Taylor & Francis Group, 2026)
This study examines how social space is produced within the context of language education for adult migrants and refugees. Drawing on ethnographic observations of classroom interactions in Finland and Germany, and utilizing Henri Lefebvre’s theory of moments (2002/1961) and the production of social space (1991/1974), the study explores markers of social affiliation and atmosphere that are essential for active participation in a new linguistic environment.